1984
DOI: 10.1002/ana.410160116
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte interferon administration to patients with symptomatic and suspected rabies

Abstract: Body fluids and brain tissue from rabid human patients have demonstrated only low titers of interferon. Therefore, pharmacokinetic studies of systemically administered and locally injected leukocyte interferon were performed in 2 North American patients with suspected rabies who showed no clinically important side effects of this therapy. Similar therapy was given to 5 patients with symptomatic rabies in Europe and America. Although no prolongation of the clinical course was seen in 3 patients given high-dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Although some antiviral drugs such as ribavirine are found effective in experimental animals, they were ineffective in treating human cases. [54] Same results have been observed with Interferon[55] and high doses of intrathecally administered rabies immunoglobulin. [56] Cases of furious rabies should be isolated and sedated and allowed to depart his/her life peacefully.…”
Section: Treatment and Management Of Rabies Patientsmentioning
confidence: 62%
“…Although some antiviral drugs such as ribavirine are found effective in experimental animals, they were ineffective in treating human cases. [54] Same results have been observed with Interferon[55] and high doses of intrathecally administered rabies immunoglobulin. [56] Cases of furious rabies should be isolated and sedated and allowed to depart his/her life peacefully.…”
Section: Treatment and Management Of Rabies Patientsmentioning
confidence: 62%
“…There are no established antiviral treatment regimens for rabies, although various post-exposure prophylaxis schedules based on vaccine therapy with or without rabies-specific immunoglobulins are being used to prevent development of symptomatic disease. Some PK studies have been performed on the kinetics of administered anti-rabies antibodies [17, 18] and administered human interferon to support an early immune response [100]. …”
Section: Resultsmentioning
confidence: 99%
“…Pharmacokinetics of human leukocyte interferon in CSF was compared between systemic and local intraventricular direct administration [100]. This study demonstrated that interferon levels in the CSF could be maintained at potentially therapeutically active levels, also by systemic administration.…”
Section: Resultsmentioning
confidence: 99%
“…Therapy with a single agent, such as ribavirin or IFN-a, has been unsuccessful [15,16], although it is possible that a combination of specific therapies may be more effective. This approach-with the use of, for example, vidarabine and IFN-has been tried for patients with a late stage of disease [17].…”
Section: Combination Therapymentioning
confidence: 99%